Anti-Corruption Education Policy At Marshal Suryarama Aerospace University Based On Regulation Of The Minister Of Research, Technology And Higher Education No. 33/2019 On The Implementation Of Anti-Corruption Education In Higher Education - Ardison Asri; Aria Caesar Kusuma Atmaja; Lasmauli Noverita; Arya Budi Pratama; Zeta Claudia sandra siregar (JURNAL HUKUM SEHASEN, 2024)
Anti-corruption education is an effort to reform political culture through the education system to make sustainable cultural changes, including to encourage the creation of a good governance culture in schools and universities. For higher education, the Directorate General of Higher Education of the Ministry of Education and Culture issued Circular Letter Number 1016/E/T/2012 dated July 30, 2012 jo. Regulation of the Minister of Research, Technology, and Higher Education Number 33 of 2019 on the Implementation of Anti-Corruption Education in Higher Education which emphasizes to State Universities and Private Universities to organize Anti-Corruption Education starting in 2012/2013 in the form of Mandatory / Elective Courses or inserted in relevant courses. Therefore, it is very interesting to examine how the anti-corruption education model policy at Marshal Suryadarma Aerospace University. To answer these problems, a normative juridical research method supported by empirical research is used. From the results of the research, it is found that anti-corruption education is very necessary to be given to students in the Elementya environment. Regarding the policy model, there are those who think that anti-corruption education needs to be taught as a separate course, but there are those who think that anti-corruption education is sufficiently inserted or integrated with other courses.